As representações do intelectual na correspondência entre Jorge de Sena e Vergílio Ferreira ― (1950‐1975) - Pereira, Marcio Roberto [UNESP] (My University, 2013)
The purpose of this article is to discuss the representations of intellectual in the epistolary production of Jorge de Sena (1919‐1978), more specifically in correspondence with Virgil Ferreira (1916‐1997), which occurred between the years 1950 to 1975. Some topics, such as the condition of intellectual dictatorship, the position of the writer and his relations with the aesthetics of Neo‐Realism and the condition of exile, are important topics that make up most of the concerns of both writers.

El propósito de este artículo es analizar las representaciones del intelectual en la producción epistolar de Jorge de Sena (1919‐1978), más concretamente en correspondencia con Virgilio Ferreira (1916‐1997), que tuvo lugar entre los años 1950‐ 1975. Algunos temas, como la condición de la dictadura intelectual, la posición del escritor y sus relaciones con la estética del neorrealismo y la condición del exilio, son temas importantes que componen la mayor parte de las preocupaciones de ambos escritores.

A proposta deste artigo é discutir as representações do intelectual na produção epistolar de Jorge de Sena (1919-1978), mais especificamente na correspondência com Vergílio Ferreira (1916-1997), ocorrida entre os anos de 1950 a 1975. Alguns temas, como a condição do intelectual em tempos de ditadura, a posição do escritor e suas relações com a estética do Neo-realismo e a condição do exílio, são importantes assuntos que compõem grande parte das preocupações de ambos os escritores.
Keywords: Letters; Exile; Memory; Intelectual; Cartas; El exilio; La memoria; El intelectual; Cartas; Exílio; Memória; Intelectual